Teknik Cilukba Dan Teknik Empat Pola Pikir Matematika Untuk Menulis Cerita Pendek - Pana Pramulia (Universitas Negeri Surabaya, 2019)
Literary works are based on the author's experience through an experienced event, as well as psychiatric experiences to respond to events. Before writing literary works, the writer makes further contemplations and studies, so that the results of his work are useful and inspiring the reader. The process of contemplation and study of events and psychology can be regarded as an imaginative process. The imaginative process requires constant practice and practice, so that the ideas possessed by a writer can provide an explosion and motivation. For beginner writers, this is not easy. Beginner writers need special techniques as a step for composing literary texts. For beginner writers there are many techniques offered by experts. Two of the many, is the mindset of the cilukba pattern and four mathematical pattern. The mindset of the cilukba has a function to create a framework of ideas. Four mathematical thought patterns function as tools for selecting diction and developing an idea framework. These two mindsets were applied by PGSD students at PGRI Adi Buana University Surabaya Class of 2015 to write short stories. After using the cilukba mindset and four mathematical mindset, students succeeded in making short stories based on predetermined rules. The 23 short stories collected were then compiled into an ISBN short story anthology book.